A Conserved Gcn2-Gcn4 Axis Links Methionine Utilization and the Oxidative Stress Response in Cryptococcus neoformans - Stovall, Anna K.; Knowles, Corey M.; Kalem, Murat C.; Panepinto, John C. (Frontiers in Fungal Biology, 2021)
The fungal pathogen Cryptococcus neoformans relies on post-transcriptional mechanisms of gene regulation to adapt to stressors it encounters in the human host, such as oxidative stress and nutrient limitation. The kinase Gcn2 regulates translation in response to stress by phosphorylating the initiation factor eIF2, and it is a crucial factor in withstanding oxidative stress in C. neoformans, and amino acid limitation in many fungal species. However, little is known about the role of Gcn2 in nitrogen limitation in C. neoformans. In this study, we demonstrate that Gcn2 is required for C. neoformans to utilize methionine as a source of nitrogen, and that the presence of methionine as a sole nitrogen source induces eIF2 phosphorylation. The stress imposed by methionine leads to an oxidative stress response at both the levels of transcription and translation, as seen through polysome profiling as well as increased abundance of select oxidative stress response transcripts. The transcription factor Gcn4 is also required for methionine utilization and oxidative stress resistance, and RT-qPCR data suggests that it regulates expression of certain transcripts in response to oxidative stress. The results of this study suggest a connection between nitrogen metabolism and oxidative stress in C. neoformans that is mediated by Gcn4, possibly indicating the presence of a compound stress response in this clinically important fungal pathogen.